1974
DOI: 10.1037/h0037428
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement delay: A selective review of the last decade.

Abstract: A review of data and theories on delay of primary reinforcement in discrete trial instrumental learning is provided. The major areas of investigation that are reviewed include delay of negative reinforcement; measurements of delay effects; cue utilization in acquisition and extinction; resistance to extinction as a function of constant delay, partial delay, patterns of partial delay; contrast; and discrimination learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
1
6

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 89 publications
2
47
1
6
Order By: Relevance
“…As with other behavioral variables, similar effects have been found using the methods of the experimental analysis of behavior and using traditional research designs (e.g., Renner, 1964;Tarpy & Sawabini, 1974). The focus of these latter designs, however, has been primarily on the effects of reinforcement delay on acquisition and extinction, whereas the former has been on response maintenance.…”
Section: Discussionmentioning
confidence: 63%
“…As with other behavioral variables, similar effects have been found using the methods of the experimental analysis of behavior and using traditional research designs (e.g., Renner, 1964;Tarpy & Sawabini, 1974). The focus of these latter designs, however, has been primarily on the effects of reinforcement delay on acquisition and extinction, whereas the former has been on response maintenance.…”
Section: Discussionmentioning
confidence: 63%
“…Second, a secondary reinforcer could provide immediate reinforcement and thus generate in C animals, but not in R subjects, the same behavioral outcomes that are normally associated with immediate primary reinforcement. It is well known, for example, that a brief cue occurring between the response and delayed reward facilitates delayed-reward performance (see Tarpy & Sawabini, 1974, for a review). Third, a secondary reinforcer could bridge the temporal gap between the response and food in the same way that intervening cues operate in conventional Pavlovian conditioning experiments to produce a stronger response-reinforcer association (see Rescorla, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decades of research on operant learning have demonstrated that behavior is most effectively reinforced when knowledge of the desired response is provided immediately after the response occurs (e.g., Perin, 1943;Pubols, 1958;Tarpy & Sawabini, 1974). Interestingly however, research using cognitive tasks has found that immediate feedback is not always best.…”
mentioning
confidence: 97%